An Analysis of Students Techniques in Paraphrasing at English Department Universitas Negeri Padang - Latifah Maiyoritsa; Delvi Wahyuni (Universitas Negeri Padang, 2021)
This study aims to determine the techniques used by students in paraphrasing, the level of paraphrasing ability and also the problems faced by students in paraphrasing in the academic writing class of the English Department of UNP. This research uses descriptive qualitative. The people who took part in this research activity were 126 students of the acamic writing class of the English Department of UNP for the 2019 academic year. The instruments used in this study were tests and questionnaires. In this study found The researcher can be concluded 86 students used the synonym technique, 12 students used make abstract ideas concreate, 20 students used divide long sentences and 8 students used omit any unnecessary. The score of paraphrasing test was range about 38-95. 9 students qualified in average level, 39 students qualified in good level, 67 students qualified in excellent level, and 5 students qualified in unsatisfactory